Ag-stabilized few-layer graphene dispersions in low boiling point solvents for versatile nonlinear optical applications - Sun, Zhenyu; Dong, Ningning; Wang, Kangpeng; König, Dennis; Nagaiah, Tharamani Chikka; Sánchez, Miguel D.; Ludwig, Alfred; Cheng, Xin; Schuhmann, Wolfgang; Wang, Jun; Muhler, Martin (Carbon (New York), 2013)
A solution stabilization strategy that uses an easily removable media is critical to graphene (G) applications. Here, we demonstrate that highly stable graphene dispersions in low boiling point solvents such as isopropanol can be readily achieved by the uniform deposition of Ag nanoparticles (NPs) on the surface of graphene. Optimizing the synthesis parameters such as ultrasonic intensity, feeding strategy, loading content and precursor concentration allowed us to tune the particle size and, in this way, the stabilizing effects of the NPs on the dispersions. The as-obtained Ag/G/i-PrOH dispersions exhibit versatile nonlinear optical properties suggesting a great potential in nanophotonic applications such as absorber for ultrafast lasers and eye protection.